PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS X2 SMA NEGERI 1 TANAH MERAH - Hanifah Amatullah; Sehatta Saragih; Atma Murni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is a class action research that aims to improve thelearning process and to improve the student’s mathematical problem solving ability byapplying Problem Based Learning (PBL). The subjects of this research are the studentof class X2 Senior High School 1 Tanah merah at first semester of academic years2015/2016, which amounts to 29 students. This research consists of two cycles, eachcycle consists of four stages: planning, implementation, observation, and reflection.Data collected through observation and student’s mathematical problem solving abilitytest. Data analysis is done by observation data analysis and student’s mathematicalproblem solving ability data analysis. The action is successful if the scores of teacher’sactivities and student’s activities increase in every meeting, improve the student’smathematical problem solving ability every cycle and improve the classical’smathematical problem solving ability. The result of observation show teacher andstudents activities are improve better than before in every meeting. Based on dataanalisys of student’s mathematical problem solving ability test show the average N-gainof student’s mathematical problem solving ability in first cycle has improve 0,26, itsmean the student’s mathematical problem solving ability in low classification and insecond cycle the average N-gain of student’s mathematical problem solving ability hasimprove 0,39, its mean the student’s mathematical problem solving ability in mediumclassification. The average score of classical’s mathematical problem solving abilityhas improve 31,46 in first cycle than beginning test and the average score of classical’smathematical problem solving ability has improve 6,15 in second cycle than first cycle.The result of this research showed that Problem Based Learning improve the learningprocess and increase the the student’s mathematical problem solving ability of class X2Senior High School 1 Tanah merah at first semester of academic years 2015/2016.Keywords: Student’s mathematical problem solving ability, Problem Based Learning